3D GIS urban runoff mechanism: A new perspective using volumetric soft geo-object - Izham Mohamad Yusoff,; Main Rindam, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
With the enhancement of the current GIS data model into a 3D dynamic simulation form, the importance of urban runoff mechanism could be visualized significantly. Such enhancement provides a valuable step for urban runoff modelers by visualizing complex streamflow routing, overland flow, channel flow routing and runoff volume coverage information. Inclusion of Volumetric Soft Geo-objects (VSG) offers substantial effort towards representing 3D dynamic simulation of overland flow volume that hits the urban flood-plain areas, estimating channel flow capacity, routing and diversions to reduce urban flood disaster. The VSG are driven by a Kinematic Wave Routing and Green-Ampt method for simulating open channel flow and overland flow volume respectively using HEC-HMS hydrologic model. Basin model, sub-basin, reach and junction elements are extracted from Digital Elevation Model (DEM) with 5 meter resolution using HEC-GeoHMS programme within ArcView GIS software and HEC-HMS model. The comparison of simulated discharge volume using VSGs with observed 10 minutes interval discharge volume gave a reading of R2 = 0.88 and a Nash-Sutcliffe coefficient of 0.82. Such 3D VSG visualization is useful in predicting potential location of flood disaster, landslide high risk spots, and informative. It is also valued as a realistic and sustainable hydrologic impact management instrument by contemporary GIS practitioners including hydrologists, environmentalists, town planners and other relevant scientists.